PENGARUH PERTUMBUHAN MODAL DAN ASET TERHADAP RASIO RISK BASED CAPITAL (RBC), PERTUMBUHAN PREMI NETO DAN PROFITABILITAS PERUSAHAAN ASURANSI UMUM DI INDONESIA - Kirmizi '; Susi Surya Agus (PEKBIS, 2012)
he aim of this research is to identify and analyze the influence of capital and assetgrowth on RBC, the influence of capital and asset growth and RBC on PremiumGrowth, the influence of capital, asset, premium growth, and RBC on ROE offinancial performance variables in general insurance industries in the period of 2000-2007. This research was using the secondary data which was collected frominsurance financial reporting the period of 2000-2007 from Infobank ResearchDepartment. One handred and seven companies was drawn as sample.The datawas analyzed by using path analysis statistic method. Based on statictly finding, thedata can be explained by model and the research found the capital growth havenegative influence on the premium growth, the asset growth have positive influenceon premium growth, the capital growth have positive influence on Return On Equity,the asset growth have positive influence on the return on equity. The research canbe drawn conclusion that optimum capital and asset used in the companies not onlycould achieve optimum income and profits but also increase RBC ratio up to thelevel 120%. The companies also focus on Risk Management, Services, CorporateVision & Mission, and Active to higher employee’s skill and knowledge.